"ProGAS From Home" as alternative breakfast education for preventing anemia for adolescent girls during the COVID-19 pandemic in Sleman Regency - Radifan, Muhamad Almas (BKM Public Health and Community Medicine, 2021)
Objective: This study examines public health problems related to anemia prevention through breakfast education for adolescent girls by developing ProGAS (Program Gizi Anak Sekolah) that have been implemented in previous years into “ProGAS from home” that is determined from their respective homes during the pandemic. Content: Around 22.7% of Indonesian females aged between 14 and 18 years suffer from anemia, a condition that is most commonly caused by micronutrient deficiencies and malnutrition. Based on the survey results obtained from 2016 to 2018, the adolescent anemia rate in Sleman Regency tends not to experience a significant decrease. The prevalence of anemia in adolescent girls is expected to increase during the pandemic. Some of the main factors are the habit of not having breakfast, poor diet, and economic factors. Since schools were closed due to the pandemic, teenagers do not have any access to information and knowledge about nutrition and women’s health. Schools also find it difficult to provide nutrition education outside the school curriculum. In addition, youth-based health education programs are not enough with one-way communication, but also need to practice by providing breakfast as a fulfillment of nutritious and healthy food. ProGAS from home can be an alternative education that can prevent anemia in adolescent girls through habituation to breakfast in their respective homes. ProGAS which is promoted by the Ministry of Education and Culture has previously been able to meet the nutritional needs of students in several schools. In this program, it is necessary to involve local SMEs such as catering or healthy restaurants in providing breakfast. Thus, in addition to achieving the main program, it can also increase income for local SMEs who have been affected by the pandemic.